1994
DOI: 10.1177/0310057x9402200209
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Costing Methodology: Cost Benefit Analysis of Mask Continuous Positive Airway Pressure for Severe Cardiogenic Pulmonary Oedema

Abstract: Costing data for intensive care admissions is important, not only for unit funding, but also for cost outcome analysis of new therapies. This paper presents an intensive care episode costing methodology using the example of a cost-benefit analysis of mask CPAP for severe cardiogenic pulmonary oedema (CPO). This analysis examines the intervention of admitling all patients with severe CPO to the intensive care unit for mask CPAp, compared with the previous practice of admitting only patients failing conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Ridley et al [18] reported fixed costs which were 11 % of the total costs from a study carried out in the United Kingdom, Holt et al [19] reported that 26 % of the total costs for ventilated patients were fixed from a study carried out in Australia and Halpern et al [20] reported that indirect costs were 33 % of the total costs from a study carried out in the United States. In this study, we report non-patient-related costs of 49 % of the total costs of care.…”
Section: Discussionmentioning
confidence: 99%
“…Ridley et al [18] reported fixed costs which were 11 % of the total costs from a study carried out in the United Kingdom, Holt et al [19] reported that 26 % of the total costs for ventilated patients were fixed from a study carried out in Australia and Halpern et al [20] reported that indirect costs were 33 % of the total costs from a study carried out in the United States. In this study, we report non-patient-related costs of 49 % of the total costs of care.…”
Section: Discussionmentioning
confidence: 99%
“…CPAP has proven to be easier to use, quicker to implement in clinical practice and to carry smaller associated costs in comparison with non-invasive ventilation (NIV) [2]. In light of these findings, CPAP has also been also used to treat ACPE patients outside the intensive care unit or the Emergency Department, as in the general ward or during prehospital care [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing costs in intensive care are the biggest staff cost and form about 30-40% of the total costs 8,9 . Intuitively, those working at the bedside realise that a direct relationship exists between the severity of illness and the nursing time needed.…”
Section: Discussionmentioning
confidence: 99%